Epidemiological and clinical profile of Influenza A(H1N1) pdm09 in Odisha, eastern India. Issue 10 (October 2019) - Dwibedi, B.; Sabat, J.; Dixit, S.; Rathore, S.; Subhadra, S.; Panda, S.; Pati, S.S.; Mandal, M.; Ho, L.M.; Thakur, B.; Kar, S.K.
Abstract: Epidemic of flu is highly contagious and it spreads through air. In 2009 H1N1 influenza virus emerged after reassortment of North American TRIG and Eurasia Avian like virus of swine and started epidemic in Mexico. The first cases were reported from Hyderabad city on 16th May 2009 in India that spread rapidly within a short span of time. During this period large population of Odisha situated at the eastern side of India was also affected and incidences of H1N1 cases were recorded through state Government surveillance system. In this study real time RT-PCR based diagnosis was conducted for the throat swabs collected from suspected H1N1 cases in Odisha during 2009–2017. A total of 2872 throat swabs were received from 23 different Government and private hospitals and 21.1% positivity was confirmed. The disease affected mostly 46–60 years age group, males (50.6%) being more affected. The clinical features had shown that fever with cough (89.6%) was the most common symptom followed by shortness of breath (72.7%). Post monsoon was the peak season in which most of the cases were reported. Neurological signs, pregnancy, diabetes and hypertension were found to be risk factors for H1N1. The case fatality rate (CFR) was 15%. Abstract : Epidemiology; Infectious disease; Odisha; Real time RTPCR; H1N1; India